1961
DOI: 10.1121/1.1908659
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anoxia on Cochlear Potentials

Abstract: The anterior inferior cerebellar artery of guinea pigs was occluded, thereby interrupting the blood supply to the cochlea. Durations of occlusion ranged from ! through 60 min. Cochlear microphonics, summating potential, action potential, and endocochlear potential were recorded before, during, and subsequent to occlusion. The differential effect of anoxia on the various potentials was observed, as well as the appearance of the large negative dc potential in scala media as anoxia progressed. For the brief occlu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
40
1
1

Year Published

1969
1969
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(47 citation statements)
references
References 0 publications
5
40
1
1
Order By: Relevance
“…It is really surprising that the stria vascularis can recover even in part after this long period of anoxia. Konishi et al (1961) also reported the partial recovery of the EP after 60 min anoxia. Light microscopical studies along this line indicate that the stria vascularis exhibits marked damage and separation from the underlying spiral ligament within 1 hr of anoxia (Kimura and Perlman 1958).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is really surprising that the stria vascularis can recover even in part after this long period of anoxia. Konishi et al (1961) also reported the partial recovery of the EP after 60 min anoxia. Light microscopical studies along this line indicate that the stria vascularis exhibits marked damage and separation from the underlying spiral ligament within 1 hr of anoxia (Kimura and Perlman 1958).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, vascular disorder is thought to be one of the possible causes of sudden deafness, and the special attention is paid to the relation between the cochlear damage and the duration of anoxia. Investigation along this line was reported by Konishi et al (1961), but they mainly observed the effect of anoxia upon the cochlear microphonics and the action potential, and there was only a short description on the endolymphatic potential (abbr. EP).…”
mentioning
confidence: 99%
“…There is a remarkable similarity between the effects of ouabain, anoxemia (Konishi et al, 1961) and of cyanide (Konishi and Kelsey, 1968 c) on the cochlear potentials. This warrants the conclusion that the energy supply for the activity of the cation pump is supplied by the oxidative metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with the mechanical movement of the basilar membrane (von Bekesy, 1960). The CMP, like the positive ERP, has been shown to be highly dependent on oxidative metabolism (Misrahy et al, 1958 a;Konishi et al, 1961;Rice and Shinaberger, 1961;Chambers and Lucchina, 1966;Konishi and Kelsey, 1968 c), although an anoxemic fraction of about ]0 r /( persists for hours after death (Davis, 1957).…”
Section: Cochlear Microphonic Potentialmentioning
confidence: 99%
See 1 more Smart Citation